1999
DOI: 10.1021/es980468q
|View full text |Cite
|
Sign up to set email alerts
|

Nonmethane Hydrocarbon, Monocarboxylic Acid, and Low Molecular Weight Aldehyde and Ketone Emissions from Vegetation in Central New Mexico

Abstract: Direct emissions of nonmethane hydrocarbons, monocarboxylic acids, and low molecular weight carbonyl compounds were measured from vegetation typical to central New Mexico. These species included quaking aspen, cottonwood, Gambel oak, Douglas fir, Engelmann spruce, Rocky Mountain juniper, pinyon pine, and ponderosa pine. The hydrocarbon emissions from most of the coniferous trees were dominated by α-pinene. In general, α-pinene emissions were 100−10 000 ng g-1 h-1 and displayed the expected temperature dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 25 publications
(37 reference statements)
1
36
0
4
Order By: Relevance
“…As an intermediate step, MEGAN2.1 uses a simple approach with the acetaldehyde and ethanol emission factors and algorithms described by Millet et al (2010). Emission factors for formic and acetic acid are based on enclosure measurements reported by Kesselmeier et al (1997), Kreuzwieser et al (1999), Martin et al (1999) and Kesselmeier (2001) which suggest that emissions of these compounds are small, although with a large uncertainty. Sawada and Totsuka (1986) extrapolated enclosure measurements showing widespread ethene production by plants in most landscapes.…”
Section: Model Parametersmentioning
confidence: 99%
“…As an intermediate step, MEGAN2.1 uses a simple approach with the acetaldehyde and ethanol emission factors and algorithms described by Millet et al (2010). Emission factors for formic and acetic acid are based on enclosure measurements reported by Kesselmeier et al (1997), Kreuzwieser et al (1999), Martin et al (1999) and Kesselmeier (2001) which suggest that emissions of these compounds are small, although with a large uncertainty. Sawada and Totsuka (1986) extrapolated enclosure measurements showing widespread ethene production by plants in most landscapes.…”
Section: Model Parametersmentioning
confidence: 99%
“…Methanol and acetone emissions from the FACTS1 region were 0.18 and 0.11 g C m À2 yr À1 , respectively, although agricultural and harvesting emissions are not included in this estimate. Martin et al (1999) found that low molecular weight organic acids, aldehydes, and ketones were important emissions from tree species in Central New Mexico. Ambient concentrations of these compounds were in the 0.5-2 ppb range, while isoprene and monoterpene concentrations were below detection limits.…”
Section: Article In Pressmentioning
confidence: 99%
“…As recently reviewed by Seco et al (2007), significant quantities of acetaldehyde are emitted by plants to the atmosphere (Janson et al, 1999;Villanueva-Fierro et al, 2004;Hayward et al, 2004;Martin et al, 1999;Schade and Goldstein, 2001). However, the ability of plants to also act as a sink for acetaldehyde has become increasingly clear Rottenberger et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Confusingly, many studies indicate a lack of stomatal influence on exchange rates. For example, several studies concluded that acetaldehyde emissions were not correlated with any physiological parameters including stomatal conductance (Kesselmeier et al, 1997;Kesselmeier, 2001;Martin et al, 1999). When ethanol was supplied to poplar leaves, promoting production of acetaldehyde in a reaction catalyzed by alcohol dehydrogenase, no correlation could be found between stomatal conductance and acetaldehyde emissions, where variation in conductance was induced either by abscisic acid or by varying light (Kreuzwieser et al, 2001).…”
Section: Introductionmentioning
confidence: 99%